Humanity and morality reflected in louisa may alcott's little women novel (1868): a sociological approach - Pertiwi, Gayuh Putri, Dr. M. Thoyibi, M.S, Mauly Halwat Hikmat, Ph. D (2014)
The aim of this research is to analyze how the humanity and morality are expressed in the novel by using sociological approach. The objectives of the research are to analyze the novel based on the structural elements and to analyze the novel based on sociological approach. This research uses qualitative research. Data of the research are divided into two, primary data and secondary data. The primary data of the research is Little Women novel and secondary data of the research are other materials related to the study. The result of the study shows the following conclusion. Based on the analysis it shows that there is a close relation between the novel and the social reality in the second half of the nineteenth century. Louisa May Alcott wants to show that humanity and morality values are important in social life, because it can make the harmonious relation between one and the others.